2014
DOI: 10.1038/ejhg.2014.194
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous case subgroups increase power in genetic association studies

Abstract: Genome-wide association studies of clinically defined cases against controls have transformed our understanding of the genetic causes of many diseases. However, there are limitations to the simple clinical definitions used in these studies, and GWAS analyses are beginning to explore more refined phenotypes in subgroups of the existing data sets. These analyses are often performed ad hoc without considering the power requirements to justify such analyses. Here we derive expressions for the relative power of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…At least three reasons could reduce the possibility of false positives of the present results of statistically significant SNPs in cluster-based GWAS. First, the present study validated the usefulness and feasibility of the concept of a previous simulation study (8), which indicated that homogeneous case subgroups increase power in genetic association studies by Traylor and colleagues, using measurement data in the real world. Second, a substantial number of statistically significant SNPs in cluster-based GWAS observed in the present study were located within or near previously reported candidate genes for ASD (6,(38)(39)(40)(41)(42)(43).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…At least three reasons could reduce the possibility of false positives of the present results of statistically significant SNPs in cluster-based GWAS. First, the present study validated the usefulness and feasibility of the concept of a previous simulation study (8), which indicated that homogeneous case subgroups increase power in genetic association studies by Traylor and colleagues, using measurement data in the real world. Second, a substantial number of statistically significant SNPs in cluster-based GWAS observed in the present study were located within or near previously reported candidate genes for ASD (6,(38)(39)(40)(41)(42)(43).…”
Section: Discussionsupporting
confidence: 76%
“…If the heterogeneous phenotypes and responses to treatment in some way correspond to differences in genotype, grouping persons with ASD according to phenotype and responses to treatment variables may increase the chances of identifying genetic susceptibility factors. Traylor and colleagues (8) demonstrated that attempts to categorize patients with a complex disease into more homogeneous subgroups could have more power to elucidate the hidden heritability in a simulation study. Several studies on Alzheimer's disease, neuroticism, or asthma indicated that items or symptoms were to some degree more useful for identifying high-impact genetic factors than broadly defined diagnoses (9)(10)(11), although a study of ASD demonstrated modest effects of two-way stratification by individual symptoms (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other disadvantage of looking at more homogenous groups is the reduction in sample size. However, it has previously been shown that only modest increases in effect size may be required to offset the reduction in power from analyzing fewer cases, implying that analyses of more homogenous subgroups have the potential to identify novel associations (56). …”
Section: Discussionmentioning
confidence: 99%
“…However, a strategy based on the identification of genetic variants in phenotypically defined subgroups (or endophenotypes) has the potential to empower genetic research into rare conditions like EA. 6 This study describes the prevalence of cardiovascular (CV) and non-CV comorbidities in EA patients from a single CV center during a 20-year period. The results highlight some unexpected associations between different comorbidities and their relationship to disease severity and survival.…”
Section: Introductionmentioning
confidence: 99%